Quality of Life and Adverse Events: Prognostic Relationships in Long-Term Ovarian Cancer Survival. (17th March 2021) - Wenzel, Lari; Osann, Kathryn; McKinney, Chelsea; Cella, David; Fulci, Giulia; Scroggins, Mary J; Lankes, Heather A; Wang, Victoria; Nephew, Kenneth P; Maxwell, George L; Mok, Samuel C; Conrads, Thomas P; et al.
Abstract: Background: There is a critical need to identify patient characteristics associated with long-term ovarian cancer survival. Methods: Quality of life (QOL), measured by the Functional Assessment of Cancer Therapy-Ovarian-Trial Outcome Index (FACT-O-TOI), including physical, functional, and ovarian-specific subscales, was compared between long-term survivors (LTS) (8+ years) and short-term survivors (STS) (<5 years) of GOG 218 at baseline; before cycles 4, 7, 13, 21; and 6 months post-treatment using linear and longitudinal mixed models adjusted for covariates. Adverse events (AEs) were compared between survivor groups at each assessment using generalized linear models. All P values are 2-sided. Results: QOL differed statistically significantly between STS (N = 1115) and LTS (N = 260) ( P  < .001). Baseline FACT-O-TOI and FACT-O-TOI change were independently associated with long-term survival (odds ratio = 1.05, 95% confidence interval = 1.03 to 1.06 and odds ratio = 1.06, 95% confidence interval = 1.05 to 1.07, respectively). A 7-point increase in baseline QOL was associated with a 38.0% increase in probability of LTS, and a 9-point increase in QOL change was associated with a 67.0% increase in odds for LTS. QOL decreased statistically significantly with increasing AE quartiles (cycle 4 quartiles: 0-5 vs 6-8 vs 9-11 vs ≥12 AEs, P  = .01; cycle 21 quartiles: 0-2 vs 3 vs 4-5 vs ≥6 AEs, P  = .001). Further, LTS reported statistically significantly better QOL compared with STS ( P  = .03 and P  = .01, cycles 4 and 21, respectively), with similar findings across higher AE grades. Conclusions: Baseline and longitudinal QOL change scores distinguished LTS vs STS and are robust prognosticators for long-term survival. Results have trial design and supportive care implications, providing meaningful prognostic value in this understudied population.